Pro Kontra Pencabutan Hak Menduduki Jabatan Publik Bagi Pelaku Tindak Pidana Korupsi Di Indonesia - Dewa Rumphas; Nasrullah; Nurlisna; Evi Oktarina (Consensus : Jurnal Ilmu Hukum, 2022)
Corruption in Indonesia has been categorized as a dangerous offence. Indonesia is still facing an emergency problem that has not been resolved for a relatively long time. Criminals of corruption will remain invaders and enemies of society. This corruption has given rise to many perpetrators of corruption, including public officials. Officials can commit corruption because of their positions. They can cause the country to go bankrupt. methods of investigating normative jurisprudence. Another basis of the criminal law is the deprivation of the right to occupy a public office for perpetrators of corruption. According to Indonesian law, certain rights can only be withdrawn for certain criminal acts.